Prevalence of Clostridium difficile in Uncooked Ground Meat Products from Pittsburgh, Pennsylvania - Curry, Scott R. (American Society for Microbiology, 2012)
The prevalence of Clostridium difficile in retail meat samples has varied widely. The food supply may be a source for C. difficile infections. A total of 102 ground meat and sausage samples from 3 grocers in Pittsburgh, PA, were cultured for C. difficile. Brand A pork sausages were resampled between May 2011 and January 2012. Two out of 102 (2.0%) meat products initially sampled were positive for C. difficile; both were pork sausage from brand A from the same processing facility (facility A). On subsequent sampling of brand A products, 10/19 samples from processing facility A and 1/10 samples from 3 other facilities were positive for C. difficile. The isolates recovered were inferred ribotype 078, comprising 6 genotypes. The prevalence of C. difficile in retail meat may not be as high as previously reported in North America. When contamination occurs, it may be related to events at processing facilities.